Evaluation of the impact of the agricultural insurance program of PCIC on agricultural producers in region IV-A - Felino P. Lansigan; Consorcia E. Reano; Liza N. Comia; Nancy A. Tandang; Roselle V. Collado; James Roldan S. Reyes; Rachelyn S. Arana; Ronald R. Roldan; Rocky T. Marcelino; Jared Jorim O. Mendoza; Mara Sherlin DP Talento; Edrun R. Gayosa; et al. (Philippine Institute for Development Studies (PIDS), 2017)
The evaluation of the impact of agricultural insurance program of the Philippine Crop Insurance Corporation on coconut farmers in Region IV-A (CALABARZON) was conducted from October 2015 to July 2016. The main instrument for conducting impact evaluation was the Coconut Farmers Survey which covered the provinces of Batangas, Cavite, Laguna, and Quezon with a random sample of 500 coconut farmers. The 500 samples comprised the random sample of 250 matched pairs of coconut farmers. Each pair was composed of a farmer with insurance and a farmer without insurance. Farmers with insurance were classified further into two groups, namely, those with claims and those without claims. A proportional allocation scheme with groups and farm size as stratification variables was used. For each of the two insurance groups, three strata were formed defined according to farm size: Stratum 1 - 0.5 ha and below; Stratum 2 - greater than 0.5 to 1 ha; and Stratum 3 - greater than 1 ha.Farmer, farm, and household characteristics were obtained by interviewing the farmers using a structured survey questionnaire. The farmers cited the following: 1) adverse weather conditions, 2) low farm gate prices, and 3) pests and diseases as the three most important problems. Although the study was conducted to assess the impact of agricultural insurance, it was worth noting that a significant proportion of coconut farmers were not aware of existing programs such as crop insurance. The study revealed that lack of awareness among coconut farmers on the availability of insurance products was a big problem. Some of the farmers who have been granted free insurance were not aware that they were insured. Among the most common and important reasons for non-availment of crop insurance were the lack of awareness on the availability of crop insurance products, lack of information on how to process insurance documents, and the belief that there was no need for insurance.No significant differences in mean income from coconut production were observed between the two groups with insurance, with claims and without claims, across farm sizes 0.5 ha and below and greater than 0.5 to 1 ha. Significant differences were detected only for farmers with farm sizes greater than 1 ha. The results were consistent across 2014 and 2015. When pooled, no differences were obtained between the group with insurance and the group without insurance. Results showed that the only characteristic associated with whether or not the farmer is insured is if the farmer is keen on joining farmers' organizations. Although the farmers think that having insurance is advantageous, most farmers were not willing to pay any premium.
Keywords: 330; Philippines; impact evaluation; Philippine Crop Insurance Corporation; crop insurance; agricultural insurance; coconut; PCIC; CALABARZON; coconut farmers